2021
DOI: 10.1002/anie.202015979
|View full text |Cite
|
Sign up to set email alerts
|

An Enzyme‐Activatable Engineered DNAzyme Sensor for Cell‐Selective Imaging of Metal Ions

Abstract: There is intense interest in imaging intracellular metal ions because of their vital roles in many cellular processes. The challenge has been to develop chemical approaches that can detect metal ions in a cell‐type‐specific manner. Herein we report the design of an enzyme‐activatable DNAzyme sensor technology that can distinguish metal‐ion signals in tumor cells from those in normal cells both in vitro and in vivo. Specifically, the sensing activity of a traditional DNAzyme sensor was inhibited by engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 37 publications
0
82
0
Order By: Relevance
“…[15] Owing to their unique sequence programmability and RNA-cleavage activity,DNAzymes have emerged as apowerful platform for biomolecular detection as well as gene regulation in vitro and in vivo. [16][17][18][19][20][21][22][23] Previous studies have suggested that DNAnucleotides in the catalytic core are conserved for DNAzymes to maintain their cleavage efficiency. [24] Based on this property,stimuli-responsive chemical modifications such as nitrobenzyl or phenylboronate have been exploited to regulate the activity of DNAzymes.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Owing to their unique sequence programmability and RNA-cleavage activity,DNAzymes have emerged as apowerful platform for biomolecular detection as well as gene regulation in vitro and in vivo. [16][17][18][19][20][21][22][23] Previous studies have suggested that DNAnucleotides in the catalytic core are conserved for DNAzymes to maintain their cleavage efficiency. [24] Based on this property,stimuli-responsive chemical modifications such as nitrobenzyl or phenylboronate have been exploited to regulate the activity of DNAzymes.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] However, its application in living system is significantly constrained, due to the cumbersome chemical synthesis of photolabile groups on nucleobases, the limited penetration depth of light and the potential phototoxicity. As a result, the endogenous cue, such as small molecules, 24,25 RNAs, 26,27 or enzymes, 28,29 has supplement an alternative way to regulate the DNA circuits. For small molecules-activated strategy, e.g., ATP, 24 their corresponding aptamers are needed to inter-correlate with DNA circuits.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 , 19 , 20 ] Up to date, UCNPs have been processed by size regulation, host‐lattice modulation, core‐shell engineering, and surface ligands exchange and have been endowed with unique photochemical characteristics, [ 21 ] such as narrow emission bandwidth, resistance to photobleaching, long luminescence lifetime, and relatively higher photon energy. [ 22 ] Such fascinating characteristics make them promising materials to be used as biosensors, [ 23 , 24 ] imaging agents, [ 25 ] and therapeutics. [ 26 , 27 , 28 ] However,the applications of UCNPs in biomedical areas are still facing challenges due to the limited surface engineering strategies and low drug loading capacity.…”
Section: Introductionmentioning
confidence: 99%